Stakeholder Perceptions of the Pentahelix Model in the WMK-MBKM Program at Manado State Polytechnic - Emmanuel Christian Waraney Kalalo; Marcelo Sumaraw; Theresa Agnes Novia Sahelangi; Hedy Desiree Rumambi; Wenny Anggresia Ginting; Sintia Nurani Korompis; Andreuw Kristian Pantow (Research Synergy Foundation, 2026)
This study aims to analyze the implementation of the Pentahelix model in the Merdeka Belajar Kampus Merdeka Wirausaha Merdeka (MBKM-WMK) program at Manado State Polytechnic as a strategy to realize an inclusive and sustainable economy from stakeholder perception. The background of the study comes from the high youth unemployment rate and the strategic role of MSMEs in driving economic growth and employment. Through the Pentahelix model, this program is expected to optimize students' potential to create and develop local power-based businesses. This study used a mixed-methods concurrent embedded design, with a qualitative approach as the primary method and quantitative data (Likert scale) playing a complementary role in identifying perception tendencies and strengthening findings from interviews and observations. Data were obtained through interviews and questionnaires distributed to 15 respondents using a purposive sampling technique. Data were analyzed using the average score and percentage contribution of each helix in supporting inclusive and sustainable economic goals. The results showed that all elements of the Pentahelix model contributed very strongly, with percentages: academic 91%, business 91%, government 85%, community 83%, and media 90%. This collaboration increases access to capital, entrepreneurial capacity building, distribution of local products, and branding and publication of student businesses. In 2023-2024, this program is perceived to have contributed to fostering young entrepreneurs in the agriculture, fisheries, services, and tourism sectors, with participants reporting increased entrepreneurial awareness and motivation to develop MSMEs that support the local economy in North Sulawesi. Respondents assessed that the Pentahelix model applied in this study has a strong contribution to building an inclusive entrepreneurial ecosystem that aligns with the SDGs.